2015
DOI: 10.1002/pat.3540
|View full text |Cite
|
Sign up to set email alerts
|

Forensic comparison of synthetic fibers

Abstract: Polymeric fibers are one kind of trace evidence found in the crime scenes, and they play a crucial role in criminal investigation. Identification and comparison of polymeric fibers are a direct result of professional analysis. When performed properly, the analytical method used in differentiating fibers of different origins can be of high evidential value. Regular forensic examinations of synthetic fibers to determine type and subtype are based on microscopy, spectroscopy, chromatographic, and mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
(172 reference statements)
0
23
0
1
Order By: Relevance
“…Af irst implementation of RM mapping was recently shown by Fischer et al [48] Thea utomatic analysis of af ilter is not as advanced as in FPA-based micro-FTIR, but is under development. [38,49] RM enables the chemical identification of MP particles and fibers down to small sizes (1 mm), independent of their morphology.I tt od ate the only suitable method for the identification of small MP (1 mm-20 mm). Additionally,s ize fractionation of the particles,f or example,b yt he use of sieves or filters with different pore sizes, can help to optimize MP analysis.S imilarly to FTIR, it is practical to examine larger particles,w hich can be handled with tweezers (> 500 mm), directly,a nd smaller MP on the filter.Since analysis of the whole filter is very time and labor intensive,asubset of the filter area is usually examined, which then gives statistical information on the whole filter.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Af irst implementation of RM mapping was recently shown by Fischer et al [48] Thea utomatic analysis of af ilter is not as advanced as in FPA-based micro-FTIR, but is under development. [38,49] RM enables the chemical identification of MP particles and fibers down to small sizes (1 mm), independent of their morphology.I tt od ate the only suitable method for the identification of small MP (1 mm-20 mm). Additionally,s ize fractionation of the particles,f or example,b yt he use of sieves or filters with different pore sizes, can help to optimize MP analysis.S imilarly to FTIR, it is practical to examine larger particles,w hich can be handled with tweezers (> 500 mm), directly,a nd smaller MP on the filter.Since analysis of the whole filter is very time and labor intensive,asubset of the filter area is usually examined, which then gives statistical information on the whole filter.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[24] While the small diameter of fibers often prevents their identification by means of micro-FTIR, RM is suitable for this application and is widely used, for example,int he forensic sciences. [38,49] RM enables the chemical identification of MP particles and fibers down to small sizes (1 mm), independent of their morphology.I tt od ate the only suitable method for the identification of small MP (1 mm-20 mm). These MP particles seem most problematic for aquatic organisms (see Section 4).…”
Section: Mp Identification and Quantificationmentioning
confidence: 99%
“…Two different book chapters have provided an overview as well as specific applications of Raman spectroscopy to analyze fibers . Most recently, Farah et al published a review article covering the various analytical methods, including spectroscopy, that can be used for the comparison and analysis of synthetic fibers in a forensic context . It was concluded that different features of polymer fibers are probed based on the technique used, but analysis should be ‘thoroughly cross‐checked before application to case work to maximize the significance of the results before submitting a report to the court.’…”
Section: Trace Evidencementioning
confidence: 99%
“…10 μm. Während der geringe Durchmesser der Fasern ihre Analyse mit mikro‐FTIR erschwert, ist RM gut dafür geeignet und findet beispielsweise in der Forensik Anwendung …”
Section: Analytische Methodenunclassified